Obturation of A Mandibular 2nd Molar with the Help of Ultrasonic Irrigation to Clean the Lateral Canal - Hira Abbasi; Abhishek Lal; Rizwan Jouhar; Muhammad Saqib (Journal of Bahria University Medical and Dental College, 2021)
Apex of root is of great interest for endodontists mainly because of different stages involved in its development and the surrounding tissues. Mandibular molars normally consists of 2 roots, one mesial and one distal. About common occurrence, 2 canals are found in mesial root and 1 canal in the distal root. The patient was diagnosed with symptomatic irreversible pulpitis. After cleaning and shaping, the next step is obturation. Lateral canals are complex findings in the apical third of root which is characterized as a lateral canal deviating from the main canal. Normally, this lateral canal is not part of the standard root canal procedure due to the complexities, but sometimes obturation might be possible, which might affect the long-term prognosis of the tooth. Advanced skills are required to attempt and complete obturation of the lateral canal which might be a difficult task for the general practitioners.